Peran Bank Sentral Dalam Kebijakan Moneter Islam - Miftakhul Huda (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
The effectiveness of the implementation of economic activities in each country always requires the role of payment instruments that stabilize the exchange rate so that there is no inefficiency due to fluctuating prices of products and financial institutions that have the authority to regulate and determine monetary policy called the Central Bank. The objectives of the central bank's policy as the holder of monetary authority include issuing money, controlling the circulation of money to adjust the fact of economy in the real sector so that there can be a balance. Monetary policy in each government is different from looking at the conditions and realities of each economic development. In response to this, one of the monetary policies taken in the reign of the Prophet's era was to use the gold and silver standards because of the level of exchange rate stability. However, this does not necessarily apply to monetary policy in Muslim-majority countries in the modern era, including in Indonesia, due to the scarcity of raw materials for gold and silver money. In its place, fiducier money was issued whose raw material was not from silver gold and to maintain its value by helping to impose interest rates which were thus prohibited in Islam. One of the few arguments for banning this interest system is the fact that high interest rates can affect the level of demand for money, while the demand for money is not used for urgent activities such as consumption or productive activities but is more used for speculative activities.